Comparative transcriptomic and proteomic analysis reveals common molecular factors responsive to heat and drought stresses in sweetpotaoto (Ipomoea batatas) - Tang, Wei; Arisha, Mohamed Hamed; Zhang, Zhenyi; Yan, Hui; Kou, Meng; Song, Weihan; Li, Chen; Gao, Runfei; Ma, Meng; Wang, Xin; Zhang, Yungang; Li, Zongyun; et al. (Frontiers in Plant Science, 2023)
Crops are affected by various abiotic stresses, among which heat (HT) and drought (DR) stresses are the most common in summer. Many studies have been conducted on HT and DR, but relatively little is known about how drought and heat combination (DH) affects plants at molecular level. Here, we investigated the responses of sweetpotato to HT, DR, and DH stresses by RNA-seq and data-independent acquisition （DIA） technologies, using controlled experiments and the quantification of both gene and protein levels in paired samples. Twelve cDNA libraries were created under HT, DR, and DH conditions and controls. We identified 536, 389, and 907 DEGs in response to HT, DR, and DH stresses, respectively. Of these, 147 genes were common and 447 were specifically associated with DH stress. Proteomic analysis identified 1609, 1168, and 1535 DEPs under HT, DR, and DH treatments, respectively, compared with the control, of which 656 were common and 358 were exclusive to DH stress. Further analysis revealed the DEGs/DEPs were associated with heat shock proteins, carbon metabolism, phenylalanine metabolism, starch and cellulose metabolism, and plant defense, amongst others. Correlation analysis identified 6465, 6607, and 6435 co-expressed genes and proteins under HT, DR, and DH stresses respectively. In addition, a combined analysis of the transcriptomic and proteomic data identified 59, 35, and 86 significantly co-expressed DEGs and DEPs under HT, DR, and DH stresses, respectively. Especially, top 5 up-regulated co-expressed DEGs and DEPs (At5g58770, C24B11.05, Os04g0679100, BACOVA_02659 and HSP70-5) and down-regulated co-expressed DEGs and DEPs (AN3, PMT2, TUBB5, FL and CYP98A3) were identified under DH stress. This is the first study of differential genes and proteins in sweetpotato under DH stress, and it is hoped that the findings will assist in clarifying the molecular mechanisms involved in sweetpotato resistance to heat and drought stress.